Unusual Presentation of Skin Tattoo-Associated Panuveitis. (16th March 2023) - Alisi, Ludovico; Armentano, Marta; Sampalmieri, Lorenzo; Bruschi, Simone; Zito, Roberta; Iannetti, Ludovico
ABSTRACT: Aim: We report a case of a young male who developed bilateral panuveitis after extensive tattooing. Design: Case report. Methods: A 22-year-old male with a history of inflamed tattoos presented with pain in both eyes and blurred vision in the left eye. Clinical examination showed ciliary congestion, flare, vitreous cells in both eyes, and posterior synechiae in the left eye. Optic nerve was swollen in both eyes. OCT scans demonstrated subretinal blood, associated with neurosensory macular detachment in the left eye. The skin tattoo biopsy showed a granulomatous inflammation without evidence of sarcoidosis. Long-term corticosteroid therapy allowed a regression of clinical signs and symptoms with full recovery. Conclusion: TAttoo Granulomas with Uveitis (TAGU) is a syndrome with numerous clinical presentations. In our case, optic nerve head oedema and subretinal hemorrhage at the posterior pole were the presentation signs. Ophthalmologists should always consider TAGU as a diagnosis in patients with a history of inflamed tattoos.